Factors Related to Worker Performance at PMI South Jakarta City in 2024 - Febriyana, Febriyana; Simanjorang, Chandrayani (PROMOTOR, 2025)
Worker performance is a necessary factor in the progress of an agency. It is known that there are workers who show less than optimal performance at PMI South Jakarta City, so it is necessary to know what the factor in the lack of performance produced. This research aims to determine the elements related to worker performance in PMI South Jakarta City in 2024. This research uses a cross-sectional study design and analysis using the chi-square test. Sampling used a purposive sampling technique with a minimum sample of 60 respondents. The research instruments used include NASA – TLX, MWMS, DOCS, and IWPQ. The results show that organizational culture (p = 0.011), motivation (p = 0.022), workload (p = 0.008), and working time (p = 0.041) have a relationship with employee performance. Meanwhile, age (p = 0.362), gender (p = 0.899), last education (p = 0.940), marital status (p = 0.090), length of service (p = 0.355), and job content (p = 0.455) showed no there is a relationship with worker performance. Agencies are advised to set equal working hours by regulations and implement a reward system to increase worker motivation.